How the Use of Facebook to Start an Enterprise Facilitates Empowerment for Women in Bangladesh - Haque, Mustaqim Muhib (2020)
The use of social media platforms to open online businesses has been on the rise in recent years because of its ease of use and vast reach. Women in developing countries are also utilising social media platforms to be involved in enterprising activities. This study aims to explore how the use of Facebook to start an enterprise facilitates empowerment for women in Bangladesh. The results of this study show that Facebook enabled women to overcome barriers relating to capital requirement, as it allows businesses to open pages for free. Besides, following through the lens of empowerment it was seen that being involved in enterprising activity helps women achievement empowerment thorough financial freedom, self-dependence, improved self-confidence, increased social capital and more negotiation power in family decision making.